الإستعارة فى أغراض الشعر الجاهلي فى المفضليات : دراسة وصفية تحليلية للاستعارة التصريحية والمكنية - Mohd Shahrizal bin Nasir (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This research aims to study the two forms of metaphor (al- isti'arah) known as Explicit metaphor (al-isti'arah al-Tasrihiyyah) and Implicit metaphor (al- isti'arah al-Makniyyah) which are used in the first half of the pre-Islamic and ancient Arabic poetry, al- Mufaddaliyyat. This research is carried out by describing the forms of these metaphors to demonstrate their relevance to the theme of the poetry. The research also highlights the educational values found in these metaphors. This is done by referring to the initial goal of compiling the Arabic poetries in al-Mufaddaliyyat, which was to educate al-Mahdi, the successor of Khalifah Abu ManÎur of the Abbasid Dynasty. The researcher relies on the analytical descriptive methodology to clarify the essence of al- Mufaddaliyyat and metaphor; putting sheer emphasis on both forms of Explicit and Implicit metaphors. The methodology is used to analyse the forms of these metaphors included in the first half of al-Mufaddaliyyat, following specific steps of analysis. Finally, the researcher comes to a finding that only a small percentage of Explicit and Implicit metaphors were used in al- Mufaddaliyyat, with the Explicit metaphor being used more. The researcher also found that the majority of the points of metaphor are connected to the themes of al- Mufaddaliyyat's poetries, but on the other hand, the educational values appear clearly and consistently with the goal of al- Mufaddaliyyat's compilation.